Sexual Dysfunction in Patients With Chronic Renal Disease: Does It Improve With Renal Transplantation? - Pertuz, W.; Castaneda, D.A.; Rincon, O.; Lozano, E. (Transplantation proceedings, 2014)
Currently in the medical literature there is controversy about the role and effects of renal transplantation (RTx) on the sexual functioning of patients with terminal chronic renal disease (TCRD). There is no clear evidence of the real impact of RTx on sexual functioning in these patients. This article makes a brief summary of the literature, describing the most important clinical concepts, evaluates results, and compares the impact of renal transplantation on sexual function before and after the procedure. Medline and the Embase database were consulted; Medical Subject Headings used were “Kidney Failure, Chronic,” “Kidney Transplantation,” “Sexual Dysfunction,” “Pleasure,” “Sexual Behavior,” and “Quality of Life.” Search was limited to articles within the last 15 years. Sexual dysfunction affects almost 87% of male and 60% to 80% of female patients; 40% to 78% of male patients with RTx report a sense of improvement on global sexual function, 25% to 30% of female patients of reproductive age with RTx report improvement in sexual performance and decreasing of menstrual cycle alterations. Fewer than 10% of patients receiving an RTx reported a decrease of sexual satisfaction. Despite controversy, reviewed results show significant improvement of sexual functioning after receiving an RTx. Those who report no improvement of sexual functioning may have conditions attributable to implicit characteristics of TCRD (age, neuroendocrine/metabolic problems) and/or RTx (immunosuppressive therapy). RTx improves sexual functioning by improving sexual desire and overall sexual satisfaction. Identified determinants associated with improvement of sexual functioning are decreased prolactin serum level, age younger than 45 years, and onset of dialysis less than 6 months.